The relative age effect among Chinese junior men's tennis players and its impact on sports performance. - Yisheng Aku; Cheng-Bo Yang (PLoS ONE, 2023)
The relative age effect (RAE) has been the subject of many studies, but no relevant literature has discussed the phenomenon of RAE in Chinese tennis. Numerous studies have demonstrated that RAE significantly contributes to brain drain and other occurrences that create inequity. This paper analyzes the birth dates and year-end rankings of all male players (N = 2697) who participated in China's junior tennis tournaments (U12, U14, U16) between 2014 and 2019 and who were selected for China's National Junior Team in 2019 and 2020; the paper classifies the birth dates into quarters and semesters. One of the research objectives of this study is to analyze whether RAE exists in Chinese junior men's tennis and whether RAE exerts an effect on athletes' performance. Differences between the observed and expected birthdate distributions were tested using chi-square statistics, and subsequent calculations were tested using odds ratios. The study found that RAE was present in all Chinese junior male tennis sports groups (p<0.001). The percentages of athletes born in the first half of the year were 56.4% (U12), 60.4% (U14), and 60.4% (U16), and the percentages of those born in the first quarter were 34.1% (U12), 36.4% (U14), and 37.1% (U16). Athletes with birth dates closer to the beginning of the year had a higher probability of achieving excellent athletic performance as a result of RAE, whereas those who were born near the end of the year had a more difficult time achieving strong athletic performance.